Pengaruh Lingkungan Kerja Non Fisik Dan Kepuasan Kerja Terhadap Produktivitas Karyawan Pada Pt. Indonesia Toray Synthetics Divisi Produksi - Mira Yunihastuti; Hira Maulida (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the influence of non-physical work environment and job satisfaction on employee productivity at PT. Indonesia Toray Synthetics Production Division both partially and simultaneously. The type of research used is quantitative with data analysis methods used in this study are validity test, reliability test, classical assumption test, quantitative analysis, regression analysis, and hypothesis test. The population in this study were employees of PT. Indonesia Toray Synthetics Production Division totaling 51 respondents. The results of this study indicate that the influence of non-physical work environment variables on employee productivity from the results of the t test, Sig. value. = 0.000 <0.05 and t count (19.475) > (2.010) t table, the influence of job satisfaction variables on employee productivity from the results of the t test, Sig. value. = 0.000 < 0.05 and t count (19.475) > (2.010) t table, and the influence of non-physical work environment and job satisfaction on employee productivity from the F count value = 269.215 > F table value = 3.19, from all these variables means H0 is rejected and Ha is accepted. Thus, it can be concluded that the non-physical work environment and job satisfaction partially and simultaneously have a positive and significant influence on employee productivity at PT. Indonesia Toray Synthetics Production Division..